2020
DOI: 10.1111/1365-2435.13618
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient limitation, bioenergetics and stoichiometry: A new model to predict elemental fluxes mediated by fishes

Abstract: Energy flow and nutrient cycling dictate the functional role of organisms in ecosystems. Fishes are key vectors of carbon (C), nitrogen (N) and phosphorus (P) in aquatic systems, and the quantification of elemental fluxes is often achieved by coupling bioenergetics and stoichiometry. While nutrient limitation has been accounted for in several stoichiometric models, there is no current implementation that permits its incorporation into a bioenergetics approach to predict ingestion rates. This may lead to biased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 68 publications
1
41
0
Order By: Relevance
“…Experiments, field data, and models would need to carefully consider how to incorporate the influences of these factors to ensure that general and robust relationships are developed. An example of this is the approach taken by Schiettekatte et al (2020), whereby limiting nutrients are used as the minimum parameter for consumption and excretion rates, and factors such trophic level, life stage, and temperature are considered where possible, using well-established open-access databases. Experimental design and laboratory/ field data collection should consider that the results will be applied as model inputs, used for other species, and extrapolated spatially to estimate regional and global fish carbon flux.…”
Section: Passive Fluxmentioning
confidence: 99%
See 1 more Smart Citation
“…Experiments, field data, and models would need to carefully consider how to incorporate the influences of these factors to ensure that general and robust relationships are developed. An example of this is the approach taken by Schiettekatte et al (2020), whereby limiting nutrients are used as the minimum parameter for consumption and excretion rates, and factors such trophic level, life stage, and temperature are considered where possible, using well-established open-access databases. Experimental design and laboratory/ field data collection should consider that the results will be applied as model inputs, used for other species, and extrapolated spatially to estimate regional and global fish carbon flux.…”
Section: Passive Fluxmentioning
confidence: 99%
“…However, Cavan and Hill discuss the link between primary production, fisheries production and carbon flux through fishes. Schiettekatte et al (2020) combine C, N, and P ratios in food with minimum dietary requirements of fishes to estimate nutrient flux through fishes; however, estimates for carbon flux were not reported.…”
Section: Overcoming Challenges In Measuring Fish‐based Carbon Fluxmentioning
confidence: 99%
“…105 Nutrient pumps Marine vertebrates provide a vector for nutrient transport via excretion, egesta, and movement within and between habitats. 109,110 These processes can result in horizontal nutrient transfer across ecosystems, vertical mixing across the surface layer, or nutrient recycling. 111,112 Nutrients provided by marine vertebrates can be a source of nutrition for other animals, enabling maintenance of healthy populations that store C in biomass.…”
Section: Reviewmentioning
confidence: 99%
“…For example, when this review was conducted, no papers were found linking traits to nutrient cycling, even though the process of nutrient cycling is important to the productivity of the ecosystem (Allgeier et al, 2016). A notable addition to the literature addressing this gap is a paper and companion R package proposing a trait-based approach to model nutrient cycling (Schiettekatte et al, 2020). The authors use traits such as body size, life stage, and diet to model fish ingestion and excretion rates, and accurately predict these rates for three species.…”
Section: Gaps In the Literaturementioning
confidence: 99%